Numerical modelling for effect of water curtain in mitigating toxic gas release - Min, Dong Seok; Choi, Shinhee; Oh, Eui young; Lee, Jechan; Lee, Chang Gu; Choi, Kwon young; Jung, Seungho (Journal of Loss Prevention in the Process Industries, 2020)
Hydrogen fluoride and ammonia are widely used in chemical industries. Both substances are hazardous and frequently a source of leakage accidents. Since a hydrogen fluoride release accident occurred in Gumi, S. Korea (2012), the Korea Occupational Safety and Health Agency (KOSHA) has emphasized that special attention and management are needed with respect to toxic substances. For post-release mitigation, a water curtain is known as one of the most effective and economical systems. In this study, a computational fluid dynamics (CFD) program was used to identify the effect of using a water curtain as a mitigation system for toxic substances that leak out from industrial facilities. Simulations were conducted to analyze how effectively a water curtain could mitigate the dispersion of toxic substances. To verify the simulation's accuracy, the INERIS Ammonia dispersion experiment and Goldfish experiment were simulated and compared. Various water curtains were applied to the simulated field experiment to confirm the mitigation factors with toxic substances. The results show that the simulations and experiments are consistent and that the dispersion of toxic substances can be mitigated by water curtains in certain circumstances.
Keywords: Economical systems; Gas dispersion; Hydrogen fluoride; Industrial facilities; Mitigation; Mitigation systems; Occupational safety and health; Water curtains; Ammonia; CFD; Gas dispersion; Hydrogen fluoride; Mitigation; Water curtain